ANALGESIC EFFECT OF EXTRACT ETHYL ACETATE OF MANGO LEAVES (mangifera indica L.) ON MALE MICE WITH ACETIC ACID INDUCTIONAA - Adel lisa (LPPM Universitas dr. Soebandi, 2025)
Pain is an emotionally and sensory exhausting ordeal accompanied by painful physical injury. Mefenamic acid is one example of a substance that can be used to administer pain medications. On the other hand, side effects can occur with continuous and long-term use. The analgesic effect is provided by tannins, alkaloids, saponins, and flavonoids found in mango leaves (Mangifera Indica L.). This study aims to determine the analgesic effect of ethyl acetate extract of mango leaf (Mangifera Indica L.) in male mice induced by acetic acid 1 %. Experimental setting in a controlled environment with male mice randomly placed in one of five groups. Providing negative control (CMC Na), positive control (mefenamic acid 65 mg/kgBB), and EEADM (doses 100 mg/kgBB, 200 mg/kgBB, and 300 mg/kgBB) orally were used. Only 30 minutes remained. Next, 1% acetic acid is inserted intraperitoneally. After the first 30 minutes, check the squirrels every 5 minutes. Data on squirming and percentage of protection were subsequently examined using the ANOVA SPSS test, which had a significance rate of 95% (p <0.05). Next, an LSD test was performed. In the results of the squirming test and the percent protection test using the ANOVA test , a significance value of < 0.05 was obtained, followed by the LSD test. The results of the LSD test by comparing the positive control of mefenamic acid 65 mg/kgBB with the EEADM dose of 300 mg/kggBB which showed that there was no difference in significance, this indicates that the EEADM dose of 300 mg/kgBB can be used as an analgesic. Based on the results of the study with a discussion that is known that the dose that has a faster reduction in pain is EEADM dose of 300 mg/kgBB.